Population study evaluating fracture risk among patients with chronic osteomyelitis. - Chyi Lo; Fung-Chang Sung; Chih-Hsin Mou; Tzu-Chieh Lin; Chun-Huang Tseng; Ya-Ling Tzeng (PLoS ONE, 2017)
BACKGROUND:Studies investigating the fracture risk in patients with chronic osteomyelitis (COM) limited to case reports. This study evaluated the association between COM and subsequent fracture risk using population-based data. METHODS:A subset claims data of the Taiwan National Health Insurance was used to identify 7,147 patients with COM newly diagnosed in 1999-2005 without fracture history and 28,588 general population controls, frequency matched by sex, age and diagnosis date. The incident fractures was measured by the end of 2013. RESULTS:The incidence density of fracture was 1.94-fold greater in the COM cohort than in controls (21.5 vs. 11.1 per 1000 person-years), with the adjusted hazard ratio (HR) of 1.81 (95% CI: 1.67-1.95) for COM patients compared to controls after controlling for sex, age, and comorbidities of diabetes, osteoporosis, depression and end-stage renal disease in Cox proportional hazards regression. The fracture risk increased with age and women were at greater risk than men. The fracture incidence increased substantially in those with osteoporosis, 40.2 per 1000 person-years in COM patients. Site specific analysis showed a higher portion of incident fractures for lower limbs, 52.7% in COM cohort and 46.3% in controls. CONCLUSION:Findings in this 15-year follow-up observation support our hypothesis that patients with COM are at an elevated risk of subsequent fracture. COM patients and the elderly deserve adequate consultation and awareness for fracture prevention.